The lipoxygenase gene ALOXE3 implicated in skin differentiation encodes a hydroperoxide isomerase - Yu, Zheyong (National Academy of Sciences, 2003)
Lipoxygenase (LOX) enzymes form fatty acid hydroperoxides used in membrane remodeling and cell signaling. Mammalian epidermal LOX type 3 (eLOX3) is distinctive in totally lacking this typical oxygenase activity. Surprisingly, genetic evidence has linked mutations in eLOX3 or a colocalizing enzyme, 12R-LOX, to disruption of the normal permeability barrier of the skin [Jobard, F., Lefèvre, C., Karaduman, A., Blanchet-Bardon, C., Emre, S., Weissenbach, J., Özgüc, M., Lathrop, M., Prud'homme, J. F. & Fischer, J. (2002) Hum. Mol. Genet. 11, 107–113]. Herein we identify a logical link of the biochemistry to the genetics. eLOX3 functions as a hydroperoxide isomerase (epoxyalcohol synthase) by using the product of 12R-LOX as the preferred substrate. 12R-Hydroperoxyeicosatetraenoic acid (12R-HPETE) is converted to 8R-hydroxy-11R,12R-epoxyeicosa-5Z,9E,14Z-trienoic acid, one of the isomers of hepoxilin A(3), and to 12-ketoeicosatetraenoic acid in a 2:1 ratio. Other hydroperoxides, including 8R-HPETE, 12S-HPETE, and 15S-HPETE, as well as the 13S- and 13R-hydroperoxides of linoleic acid are converted less efficiently. Mass spectrometric analysis of the epoxyalcohol formed from [(18)O]15S-HPETE showed that both hydroperoxy oxygens are retained in the product. We propose that the ferrous form of eLOX3 initiates a redox cycle, unprecedented among LOX in being autocatalytic, in which the hydroperoxy substrate is isomerized to the epoxyalcohol or keto product. Our results provide strong biochemical evidence for a functional linkage of 12R-LOX and eLOX3 and clues into skin biochemistry and the etiology of ichthyosiform diseases in humans.